Advanced Path Planning for Mobile Entities - Róka, Rastislav (IntechOpen, 2018)
The book Advanced Path Planning for Mobile Entities provides a platform for practicing researchers, academics, PhD students, and other scientists to design, analyze, evaluate, process, and implement diversiform issues of path planning, including algorithms for multipath and mobile planning and path planning for mobile robots. The nine chapters of the book demonstrate capabilities of advanced path planning for mobile entities to solve scientific and engineering problems with varied degree of complexity.